Polymorphisms in key bone modulator cytokines genes influence bisphosphonates therapy in postmenopausal women. - Lima, C A D; Javorski, N R; Souza, A P O; Barbosa, A D; Valença, A P M C; Crovella, S; Souza, P R E; de Azevêdo Silva, J; Sandrin-Garcia, P (Inflammopharmacology, 2017)
Osteoporosis is a multifactorial and debilitating disease resulting from decreased bone mineral density (BMD) and loss of tissue microarchitecture. Ineffective therapies may lead to bone fractures and subsequent death. Single nucleotide polymorphisms (SNPs) in key immune regulator genes have been associated with therapeutic response to bisphosphonates, which are the first therapeutic line of choice for osteoporosis. However, cytokine pathways and their relation with therapeutic adhesion remain to be fully elucidated. Aimed at better understanding these processes, we investigated the response to bisphosphonate therapy in postmenopausal women and four SNPs in key proinflammatory cytokines genes: IL23R +2284 (C>A) (rs10889677), IL17A +672 (G>A) (rs7747909), IL12B +1188 (T>G) (rs3212227) and INF-γ -1616 (G>A) (rs2069705). A total of 69 patients treated with bisphosphonate were followed for a period of 1 up to 4 years, genotyped and compared according to their changes in bone mineral density (BMD) and level of biochemical markers during their treatment. The INF-γ -1616 G/G associated with increased BMD values in femoral neck (GG/AA, p = 0.016) and decreased BMD values in total hip (GG/GA, p = 0.019; GG/AA, p = 0.011). In relation to biochemical markers, INF-γ -1616 SNP associated with increased alkaline phosphatase (GG/AA; p < 0.0001) and parathyroid hormone levels (AA/GA; p = 0.017). Vitamin D values changes were related to IL17A +672 (GG/GA, p = 0.034) and to IL12B +1188 (TT/TG, p = 0.046) SNPs. Besides, significant differences in changes of calcium levels correlated with IL23R +2284 (CC/CA, p = 0.016) genotypes. Altogether, we suggest that these polymorphisms may play an important role for therapeutic decisions in osteoporosis treatment.
Keywords: Aged; Bone Density; Bone Remodeling; Cytokines; Diphosphonates; Female; Humans; Middle Aged; Osteoporosis, Postmenopausal; Polymorphism, Single Nucleotide; Postmenopause